Formation Character Based On Philosophy Of Sapta Bayu: Spirit Sri Kesari Warmadewa - Putu Yudha Asteria PUTRI (International Journal of Environmental, Sustainability, and Social Science, 2021)
This paper explains the philosophy of the Meaning of Sapta Bayu Spirit Sri Kesari Warmadewa which is an abstract form of value points from Raja Sri Kesari Warmadewa. This research uses a qualitative approach, with an interpretive approach and a critical paradigm. In this paper, the assumptions of interpretive philosophy are used as a paradigm that has characteristics for understanding and explaining the social world. Sapta Bayu value points, namely (1) God Almighty; (2) Developing Asta Brata's Spirit of Leadership; (3) Serving Almamater, Society, Nation and State; (4) Excellence in work; (5) Upholding Honesty and Self Integrity in Thinking, Saying, and Acting; (6) Maintaining and Respecting Diversity to Strengthen Unity, and (7) Environmentally Friendly, based on the Tri Hita Karana instilled in Warmadewa University academicians who in this paper specialize in Accounting Students who are deemed necessary to instill local cultural values. policies to be applied later in professional accountant practice.